2012
DOI: 10.3109/09537104.2012.749396
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of platelet-mediated arterial thrombosis and platelet granule exocytosis by 3′,4′-dihydroxyflavonol and quercetin

Abstract: Flavonols are polyphenolic compounds with broad-spectrum kinase inhibitory, as well as potent anti-oxidant and anti-inflammatory properties. Anti-platelet potential of quercetin (Que) and several related flavonoids have been reported; however, few studies have assessed the ability of flavonols to inhibit exocytosis of different platelet granules or to inhibit thrombus formation in vivo. 3',4'-Dihydroxyflavonol (DiOHF) is a flavonol which is structurally related to Que and has been shown to have greater anti-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(66 reference statements)
0
18
0
1
Order By: Relevance
“…including in vitro platelet activation, in vivo thrombosis inhibition [21][22][23][24] and human interventional studies on CVDs [25][26][27][28] of quercetin, and in vitro platelet activation inhibition [29] of quercetin-3-O-β-D-glucoside have been reported in dozens of research papers, few or no reports exist on the in vitro actions of quercetin and quercetin-3-O-β-D-glucoside on procoagulant proteinases, fibrin polymer formation, and blood clot, the in vitro and ex vivo anticoagulation actions of quercetin and quercetin-3-O-β-D-glucoside, or the in vivo effects of quercetin and quercetin-3-O-β-D-glucoside against arterial thrombosis and acute thromboembolism models and platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…including in vitro platelet activation, in vivo thrombosis inhibition [21][22][23][24] and human interventional studies on CVDs [25][26][27][28] of quercetin, and in vitro platelet activation inhibition [29] of quercetin-3-O-β-D-glucoside have been reported in dozens of research papers, few or no reports exist on the in vitro actions of quercetin and quercetin-3-O-β-D-glucoside on procoagulant proteinases, fibrin polymer formation, and blood clot, the in vitro and ex vivo anticoagulation actions of quercetin and quercetin-3-O-β-D-glucoside, or the in vivo effects of quercetin and quercetin-3-O-β-D-glucoside against arterial thrombosis and acute thromboembolism models and platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the research conducted by Raghavendra and Akhilender Naidu (2009) proved that 100 µM concentration of quercetin would cause only 1.7% inhibition of thrombocytes aggregation. Then, the results of other investigations delivered the data which indicate that 100 µM concentration of quercetin causes more than 90% inhibition of collagen-induced thrombocytes aggregation (Mosawy et al, 2013). The available results of other investigations confirm the antiplatelet efficiency of quercetin against the processes of aggregation induced by antagonists of platelets other than collagen.…”
Section: Anti-aggregation Activitymentioning
confidence: 73%
“…The available results of other investigations confirm the antiplatelet efficiency of quercetin against the processes of aggregation induced by antagonists of platelets other than collagen. The experiment conducted by Mosawy et al (2013), found out that full inhibition of arachidonic acid induced platelet aggregation was achieved at 200 µM level of quercetin concentration. It was also proved that quercetin causes adenosine diphosphate (ADP) and epinephrine induced platelet aggregation (Islam et al, 2014).…”
Section: Anti-aggregation Activitymentioning
confidence: 99%
“…; Mosawy et al. ). Platelet function was interrogated in venous blood samples with multiple outcomes (i.e., MPAs, PAC‐1 and anti‐CD62P binding), with and without canonical platelet agonists, using sophisticated and established flow cytometry techniques (Linden ) which have been associated with cardiovascular outcome.…”
Section: Discussionmentioning
confidence: 97%